A GABA Interneuron Deficit Model of the Art of Vincent van Gogh - Turkheimer, Federico E.; Fagerholm, Erik D.; Vignando, Miriam; Dafflon, Jessica; Da Costa, Pedro F.; Dazzan, Paola; Leech, Robert (Frontiers in Psychiatry, 2020)
Vincent van Gogh was one of the most influential artists of the Western world, having shaped the post-impressionist art movement by shifting its boundaries forward into abstract expressionism. His distinctive style, which was not valued by the art-buying public during his lifetime, is nowadays one of the most sought after. However, despite the great deal of attention from academic and artistic circles, one important question remains open: was van Gogh’s original style a visual manifestation distinct from his troubled mind, or was it in fact a by-product of an impairment that resulted from the psychiatric illness that marred his entire life? In this paper, we use a previously published multi-scale model of brain function to piece together a number of disparate observations about van Gogh’s life and art. In particular, we first quantitatively analyse the brushwork of his large production of self-portraits using the image autocorrelation and demonstrate a strong association between the contrasts in the paintings, the occurrence of psychiatric symptoms, and his simultaneous use of absinthe – a strong liquor known to affect GABA alpha receptors. Secondly, we propose that van Gogh suffered from a defective function of parvalbumin interneurons, which seems likely given his family history of schizophrenia and his addiction to substances associated with GABA action. This could explain the need for the artist to increasingly amplify the contrasts in his brushwork as his disease progressed, as well as his tendency to merge aesthetic and personal experiences into a new form of abstraction.